The geo-environmental status of the European Union Priority Habitat Type "Mediterranean Temporary Ponds" in Mt. Oiti, Greece - Vasilatos, Charalampos; Anastasatou, Marianthi; Alexopoulos, John; Vassilakis, Emmanuel; Dilalos, Spyridon; Petrakis, Stelios; Delipetrou, Pinelopi; Georghiou, Kyriacos; Antonopoulou, Sofia; Stamatakis, Michael (Water, 2019)
Mediterranean temporary ponds (MTPs) constitute priority habitats under the European Union Habitats Directive, inhabited by several rare endemic species and subjected to unstable environmental conditions. Lakes and pond act as early indicators of climate change, in which alpine ecosystems are especially vulnerable. The study area is located in a mountainous Natura 2000 site of Central Greece, designated as “National Forest Park of Mt Oiti” (Ethnikos Drymos Oitis), which hosts a number of MTPs. Field sampling of soil and water carried out in four MTPs during dry and wet periods between 2012 and 2014. Electrical Resistivity Tomography (ERT) technique was used for the delineation of the subsurface geological structure. This study aims to present the current ecological status of Mt Oiti MTPs with respect to their geo-environmental characteristics, emphasizing to their indirect correlation with plant species richness. Moreover, this paper aims to address the lack of basic ecological background on MPTs network of Mt Oiti concerning their characteristics along with the pressures received from various activities. MTPs of Mt Oiti were classified according to their ecological status, by identifying the habitats’ threats and defining their geological structure, mineralogy and physiochemical parameters of each pond.